Malaysian and Indonesian Literature: A Brief Comparison - yanto yanto (English Literature Department, Adab and Humanities Faculty, 2019)
Malaysia and Indonesia have many things in common. These two countries are called ‘bangsa serumpun’ or one group nation. In terms of location, the two countries are very close. In terms of language, the two countries are also very close because they can understand each other by using bahasa melayu or Malay language. As a result of this closeness, the literature of the countries also has many similarities. This essay will compare the development of contemporary literature in these two Asian countries. This essay will also describe how the literature of the two countries influenced one another. The main focus is the similarities and the differences between their literature. To make it easy the term used in this essay to describe the two countries is nusantara. Nusantara is derived from Sansekerta’s language that describes the archipelago of Malaysia and Indonesia.